Immunocytochemical Methods and Protocols - Javois, Lorette C.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1999)
In Animal Cell Biotechnology, scientists with long-refined expertise describe cutting-edge techniques for the production of therapeutic proteins and vaccines. Capturing the major advances that have occurred in both the science and the technology of these biopharmaceuticals, this important book covers the powerful new techniques used in genetically manipulating animal cells, optimizing their growth in defined media (particularly at large- scale), avoiding contamination, and in the harvesting and analysis of cell products. Topics include basic culture facilities and methods; molecular methods for gene transfection; cell immortalization and cell fusion; and techniques for the study of cell growth, viability, metabolism, and productivity. Animal Cell Biotechnology constitutes a comprehensive manual of state-of-the-art techniques for setting up a cell culture laboratory, maintaining cell lines, and optimizing critical parameters for cell culture. This authoritative book will significantly aid researchers in developing new monoclonal antibodies, vaccines, anticancer agents, and drugs for the widest spectrum of cardiovascular, respiratory, and immune diseases.
Antibody Preparation -- Overview of Antibody Use in Immunocytochemistry -- Purification of Antibodies Using Ammonium Sulfate Fractionation or Gel Filtration -- Purification of Antibodies Using Ion-Exchange Chromatography -- Purification of Antibodies Using Affinity Chromatography -- Purification of Antibodies Using Protein A-Sepharose and FPLC -- Conjugation of Fluorochromes to Antibodies -- Biotinylation of Antibodies -- Tissue Preparation for Light Microscopic Analyses -- Overview of Cell Fixatives and Cell Membrane Permeants -- Preparation of Frozen Sections for Analysis -- Processing of Cytological Specimens -- Processing of Tissue-Culture Cells -- Processing of Tissue Specimens -- Antigen Retrieval for Immunohistochemical Reactions in Routinely Processed Paraffin Sections -- Light Microscopic Detection Systems -- Overview of Fluorochromes -- Direct Immunofluorescent Labeling of Cells -- Fluorescence Labeling of Surface Antigens of Attached or Suspended Tissue-Culture Cells -- Fluorescence Labeling of Intracellular Antigens of Attached or Suspended Tissue-Culture Cells -- Fluorescent Labeling of Surface or Intracellular Antigens in Whole-Mounts -- TUNEL Assay for Apoptotic Cells -- Overview of Fluorescence Analysis with the Confocal Microscope -- Overview of Laser Microbeam Applications as Related to Antibody Targeting -- Overview of Fluorescence Photomicrography -- Overview of Antigen Detection Through Enzymatic Activity -- The Peroxidase-Antiperoxidase (PAP) Method and Other All-Immunologic Detection Methods -- The Avidin-Biotin Complex (ABC) Method and Other Avidin-Biotin Binding Methods -- Avidin-Biotin Labeling of Cellular Antigens in Cryostat-Sectioned Tissue -- Multiple Antigen Immunostaining Procedures -- ELISA on Attachment-Dependent or Suspension Grown Cells -- Use of Immunogold with Silver Enhancement -- Fluorescence Activated Cell Sorter (FACS)Analyses -- Overview of Flow Cytometry and Fluorescent Probes for Cytometry -- Tissue Disaggregation -- Indirect Immunofluorescent Labeling of Viable Cells -- Indirect Immunofluorescent Labeling of Fixed Cells -- Fluorescent Labeling of DNA -- Deparaffinization and Processing of Pathologic Material -- Assay for Phagocytosis -- Assay for Filamentous Actin -- Assay for Chemoattractant Binding -- Assay for Oxidative Metabolism -- Colloidal Gold Detection Systems for Electron Microscopic Analyses -- Fixation and Embedding -- Preparation of Colloidal Gold -- Conjugation of Colloidal Gold to Proteins -- Colloidal Gold/Streptavidin Methods -- Pre-Embedding Labeling Methods -- Postembedding Labeling Methods -- Applications for Nucleic Acid Localization by In Situ Hybridization -- Overview of In Situ Hybridization -- In Situ Hybridization to Human Chromosomes of an Alkaline Phosphatase-Labeled Centromeric Probe -- Fluorescence In Situ Hybridization Using Whole Chromosome Library Probes -- In Situ RT-PCR and Hybridization Techniques -- Special Applications for the Clinical Laboratory -- Overview of the Clinical Immunohistochemistry Laboratory: Regulations and Troubleshooting Guidelines -- Overview of Immunocytochemical Approaches to the Differential Diagnosis of Tumors -- Overview of Automated Immunostainers.
Keywords: Biochemistry; Biochemistry, general